2003
DOI: 10.1161/01.hyp.0000088853.27673.d0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of Angiotensin II Receptors and Cardiovascular Risk in Hypertension

Abstract: Abstract-Renin-angiotensin systems may mediate cardiovascular disease pathogenesis through a balance of actions of angiotensin II on (potentially proatherogenic) constitutive type 1 (AT 1 R) and (potentially antiatherogenic) inducible type 2 (AT 2 R) receptors. We explored such potential roles in a prospective candidate gene association study. Cardiovascular end points (fatal, nonfatal, and silent myocardial infarction and coronary artery bypass surgery/angioplasty) were documented among 2579 healthy UK men (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 53 publications
5
54
0
3
Order By: Relevance
“…For example, a link has been found between the silent SNP 102C/T of the 5-HT2A receptor gene in the temporal cortex and the pathogenesis of schizophrenia [31]. Jones and colleagues have shown that silent polymorphisms of the angiotensin-2 receptor increase cardiovascular risk in hypertension [32], while Arriba-Mendez and colleagues have found that when the C allele is present in the silent SNP 927T/C, male children may be predisposed to asthma and atopic dermatitis [33]. Similarly, a silent SNP, 988C→T of the Fas gene has been shown to have significant implications in the development of papillary thyroid carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a link has been found between the silent SNP 102C/T of the 5-HT2A receptor gene in the temporal cortex and the pathogenesis of schizophrenia [31]. Jones and colleagues have shown that silent polymorphisms of the angiotensin-2 receptor increase cardiovascular risk in hypertension [32], while Arriba-Mendez and colleagues have found that when the C allele is present in the silent SNP 927T/C, male children may be predisposed to asthma and atopic dermatitis [33]. Similarly, a silent SNP, 988C→T of the Fas gene has been shown to have significant implications in the development of papillary thyroid carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…Serum ACE activity, HbA 1 c and ACE I/D, AT1R (AT1R 1166A>C) and AT2R (AT2R 1675A>G) genotypes were determined as previously reported [15,22,23]. Renin concentrations were measured by radioimmunoassay of generated angiotensin I, as was angiotensinogen in the presence of added excess of renin [24].…”
Section: Methodsmentioning
confidence: 99%
“…24,25) A number of initial studies attempted to address the possibility that polymorphisms at various candidate genes might be associated with the pathogenesis of CAD and some concluded there was a significant association between them. For example, polymorphisms in renin-angiotensin system gene polymorphisms (angiotensin-type receptor genes, angiotensin II converting enzyme genes) are well known to be associated with hypertension, 26) CAD [27][28][29][30][31] and MI, [32][33][34] though dissenting opinions still exist.…”
Section: Discussionmentioning
confidence: 99%